Similar, but Not the Same – Personal Perception and Covert Surveillance and Tracking Through The Prism of Legal Regulations, Practical Implementation And Case-Law in Slovenia - Dvojmoč, Miha; Sotlar, Andrej (Medicine, Law & Society, 2026)
State and private surveillance authorities may lawfully infringe fundamental rights when obtaining information. However, the public often mistakenly equates private detectives’ (hereinafter: detectives) personal perception with covert investigative measures used by police and intelligence services. It is essential to distinguish between these two forms of privacy interference. Detectives may use personal perception - lawful, time-limited observation from public spaces - to gather evidence for their clients. Although discreet, it is not a covert investigative act. Detectives may use imaging devices, while state authorities have broader surveillance powers. The purpose of personal perception is to develop evidence for a client, whereas covert surveillance serves criminal or intelligence objectives and entails a deeper privacy intrusion. Despite its lesser intensity, detective work must also be properly regulated and subject to oversight.